Pemilihan Jenis Sapi bagi Peternak Sapi Potong dengan Metode SMART - Gumilar Ramadhan Pangaribuan; Agus Perdana Windarto; Wida Prima Mustika; Anjar Wanto (UIN Sumatera Utara, 2019)
The Livestock Sector is one of the most promising agribusiness sectors. Selection of the right type of cow is the duty of cattle farmers to get cows with quality. The aim of the study was to recommend the best type of cattle using the SMART method. Data sources were obtained by interviewing and giving questionnaires to 25 random beef cattle farmers in the parbalogan village, Tanah Jawa Subdistrict, Simalungun Regency. The six types of cattle (alternative) are used such as Lemosin (A1), Simental (A2), Bali (A3), Dairy (A4), Brahma (A5) and Madras (A6). While the assessment criteria are used, namely: Origin (C1), Price (C2), Age (C3), Weight (C4), and Size (C5). The results of the study state that the type of Lemosin (A1) Beef is the first recommendation with the final value of 1 and the type of Bali cow (A3) as the second recommendation with the final value of 0.702543.. Keywords: DSS, Beef, Breeders, SMART Method, Pematangsiantar